Universiti Malaysia Sabah (UMS): towards maximizing the potential of its Human Resource Development (HRD) - Mohd. Yusof Kasim; Kasim Mansur; Abd. Razak Ahmad (2009)
As strategic education agenda works to prepare competent graduates, human resource development has become crucial for uplifting the internal strength of the university. University Malaysia Sabah (UMS) relatively a ‘young’ university has been engaged in establishing learning interaction among its staffs towards excellence. This paradigm is paramount to the strategic human resource provider as it allows not only the students who will be graduating but the young faculty members and its administrative staffs to excel. The purpose of this paper is to discuss the keys to successful university undertaken by UMS. In less than ten years, the faculty members as well as the administrative staffs manage to position the university at par to that of other established higher learning institutions in the nation. With the establishment of learning interaction, human resource development of UMS have shown some impact for promoting educational excellence among Malaysians. Indeed competent human resource plays an important role to meet the vision and the mission of UMS- strive to excel.